2022
DOI: 10.3389/fnut.2022.1000116
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-based functional films for packaging applications: A review

Abstract: Food packaging is a coordinated system comprising food processing, protection from contamination and adulteration, transportation and storage, and distribution and consumption at optimal cost with a minimum environmental impact to the packed food commodity. Active packaging involves deliberate addition of the functional ingredients either in the film or the package headspace to preserve the food quality, improve safety and nutrition aspects, and enhance the shelf-life. In this review, recent advances in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 165 publications
0
22
0
Order By: Relevance
“…Incorporating essential oils into biodegradable polymers forms active food packaging or coatings, which means that such packaging contains active substances that protect food from spoilage and prolong the shelf life of the products. The role of active compounds is to remove harmful agents, such as oxygen, moisture, and many others [ 74 , 75 ]. The components of essential oils possess antioxidant, antibacterial, and antifungal properties, which is an advantage in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating essential oils into biodegradable polymers forms active food packaging or coatings, which means that such packaging contains active substances that protect food from spoilage and prolong the shelf life of the products. The role of active compounds is to remove harmful agents, such as oxygen, moisture, and many others [ 74 , 75 ]. The components of essential oils possess antioxidant, antibacterial, and antifungal properties, which is an advantage in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…1,4,45 According to their source and production method, the biopolymers are divided into three groups: Group-I: directly extracted from biomass (polysaccharide, protein, polypeptide and polynucleotide), Group-II: produced using renewable bio-based monomers or mixed sources of biomass and petroleum, by classical chemical synthesis (poly-lactic acid, biopolyester) and Group-III: produced by microorganism or genetically modified bacteria (poly-hydroxy butyrate, bacterial cellulose, xanthene and pullulan). 26,29,44,46,47 Based on their responsiveness to the thermal conditions, they are divided into elastomers, thermo-sets and thermoplastics. Based on their composition, they are divided into blends, laminates and composites.…”
Section: Classification Of Biopolymersmentioning
confidence: 99%
“…Tong et al reported the glycerol addition to reduce the tensile strength and water barrier properties along with increase in the elongation at break and water solubility. 59 While studying the effect of various plasticisers and cross-linkers on extruded films, decrease in ultimate tensile strength on addition of glycerol plasticiser F I G U R E 3 Broad classification of biopolymers 26,29,44,[46][47][48] T A B L E 1 Types and origin of different biopolymers 4,26,29,44,[49][50][51][52][53] Types and origin of different biopolymers and derivatives…”
Section: Plasticisers and Cross-linking Agents For Biopolymersmentioning
confidence: 99%
“…These applications include manufacturing consumer specialty products such as edible food films and coatings, and developments of biobased adhesives, biodegradable membranes, and antimicrobial films. 46,[51][52][53][54][55][56][57] Owing to the diverse applications of pectin, its global market share was estimated at USD 1 billion in 2019 and is projected to be USD 1.5 billion by 2025. 15 Hydroponic cultivation 59 is a type of soilless agricultural practice for growing food crops in areas (such as in metropolitan cities and deserts) where water and land availability is inadequate for farming.…”
Section: Introductionmentioning
confidence: 99%
“…These applications include manufacturing consumer specialty products such as edible food films and coatings, and developments of bio-based adhesives, biodegradable membranes, and antimicrobial films. 46,51–57 Owing to the diverse applications of pectin, its global market share was estimated at USD 1 billion in 2019 and is projected to be USD 1.5 billion by 2025. 58…”
Section: Introductionmentioning
confidence: 99%